Development and validation of the PPROQ3-SF: A revised and shorter version of the theory-informed Person's Positive Relating to Others Questionnaire - Αργυρούλα Καλαϊτζάκη; Εμμανουήλ Μπενιουδάκης; Ιωάννης Νέστορος (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας)
Relating Theory conceptualizes and assesses relating (both negative and positive) around a two-dimensional model with four main and four intermediate positions/dimensions, graphically represented as an octagon (clockwise: upper neutral, upper close, neutral close, lower close, lower neutral, lower distant, neutral distant, and upper distant). Drawing from this theory and considering the psychometric limitations of the formerly developed, theoretically informed questionnaire (i.e., the Person's Positive Relating to Others Questionnaire; PPROQ), this study aimed to refine its items profoundly and improve its psychometric properties. Undergoing a three-step item construction, refinement, shortening, and three respective validation studies of the sequential versions (i.e., PPROQ2, PPROQ3, and PPROQ3-SF, respectively), the revised and shorter 24-item PPROQ3-SF was eventually developed. The eight-factor structure and the internal consistency of the eight scales were significantly improved across the successive versions. Test-retest reliability was also confirmed for the PPROQ3-SF. High correlations (inter-item, corrected item-total, between pairs of neighboring scales) established convergent validity, whereas low inter-scale correlations between pairs of opposite octant scales, Heterotrait-monotrait ratio of correlation, and differences across gender and chronic disease status, established discriminant validity. The final 24-item shortened version demonstrated good psychometric properties, reflecting the pre-defined eight-factor structure of the interpersonal octagon, and exhibited satisfactory reliabilities, and convergent, and discriminant validity. Being psychometrically robust and conforming well to its grounding octagonal structure, the PROQ3-SF is recommended for use in both research and clinical practice.